(3Pjd JGQjN HZOGOs - (3CHh YHO Gddg eMeO Hf SYjO GdeYQha HGdOHjfi GdhGSWis; (3GdNWjH GdHZOGOj , CHh HcQ CMeO Hf Ydj Hf KGHJ GdNWjH GdHZOGOj,J (B463 (3g` s ((3YHO GdQMje Hf YHO Gddg Hf eMeO Hf CHdi gTGe GdbQTi GdCehi s)
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG GHJOGA hGdBNQ HdG GfJgGA s
(3BNQgG (B:s
(3jfJgi Edi Chd MQa GdMGA s
(3Pjd Hg eDdag Ydi cJGH GdSeYGfi GdPi gh Pjd Ydi JGQjN HZOGOs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B137 s
Keywords: (3GdJGQjNs